Materialization of the critical theoretical production of the area of physical education in the curriculum of basic education - Campos , Franciane Drumond Soares; Ferreira, Geyson de breu; Nunes, Moisés Silva; Silva, Weric Júnio Viana da; Portilho , Ana Paula Bernardi (Seven Editora, 2023)
The understanding of the role of Physical Education in the school environment occurred in different ways, from the influences of current curricular theories in society, it assumes different identities throughout its history, being understood from a hygienist physical education, to the search for the construction of education critical, post-critical physics. The present study seeks to understand how the curriculum is worked (interpretation, analysis, and application). Qualitative and explanatory research of data surveys. Based on the analysis, it was observed that the purpose of the Pedagogical Political Project (PPP) proposed by educational institutions is consistent with the National Common Curricular Base (BNCC). However, to act and intervene in the school curriculum, it is necessary to be in a continuous process of thinking and rethinking teacher training and practice. The training of each professor during the graduation period and the subsequent process of continuing education reflects the type of theories the professor is linked to justify his/her teaching work. Finally, factors linked to responsibilities, to the understanding of the role of the institution and the discipline as a curricular component, influence the materialization of the critical theoretical productions of the curriculum, leading physical education to stay in place "between no more and not yet". DOI:https://doi.org/10.56238/alookdevelopv1-061